Peran Organizational Citizenship Behavior sebagai Mediasi Kepercayaan Organisasional dan Perilaku Berbagi Pengetahuan - Conchita Valentina Latupapua; Novalien C Lewaherilla; Agusthina Risambessy (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2020)
The purpose of this study is to investigate the effect of organizational trust variables directly on knowledge sharing behavior as well as mediated organizational organizational behavior variables. In total, there were 56 PTS lecturer respondents in the LLDIKTI XII region that were used as samples. Data collected were analyzed using descriptive and inferential statistics, namely Structure Equation Model using Warpls 5.0. The results showed that organizational trust did not have a significant effect on knowledge sharing behavior directly and organizational trust affected knowledge sharing behavior by mediating Organizational Citizenship Behavior